Breast cancers with a HER2/CEP17 ratio of 2.0 or greater and an average HER2 copy number of less than 4.0 per cell: frequency, immunohistochemical correlation, and clinicopathological features - Zare, Somaye Y.; Lin, Leo; Alghamdi, Abrar G.; Daehne, Svenja; Roma, Andres A.; Hasteh, Farnaz; Dell'Aquila, Marie; Fadare, Oluwole (Human pathology, 2019)
The 2013 American Society of Clinical Oncology and College of American Pathologists (ASCO/CAP) guidelines classified breast cancers with a fluorescence in situ hybridization dual-probe HER2/CEP17 ratio of 2 or greater as “amplified,” inclusive of cases with a HER2 copy number less than 4. The 2018 ASCO/CAP update assigns HER2/neu status for the latter group in a fashion that is highly dependent on the associated immunohistochemical findings. Herein, the authors define the frequency, immunohistochemical correlates, and other clinicopathological features of breast cancers with HER2/CEP17 ratio of 2 or greater and HER2/neu copy number less than 4 (group A), based on an analysis of an institutional cohort assessed for HER2/neu status by both florescence in situ hybridization and immunohistochemistry and scored using 2013 ASCO/CAP criteria. Group A cases were compared with a group B of HER2/neu-amplified breast cancers with a HER2/neu copy number of 4 or greater regarding a variety of clinicopathological features. One hundred sixty-nine (14%) of 1201 cases were HER2/neu amplified, 18 (10.7%) in group A and 151 (89.3%) in group B. By immunohistochemistry, 61.1% of group A cases were HER2/neu negative, 7 (38.9%) were equivocal, and none were positive. In contrast, 66.9% of group B cases were HER2 positive (3+). We could not demonstrate statistically significant differences between the 2 groups regarding standard clinicopathological variables. In summary, our group A cases account for 1.5% of breast cancers, and 10.7% of all HER2/neu-amplified cancers classified as such based on 2013 ASCO/CAP criteria. They are predominantly HER2/neu negative by immunohistochemistry, which suggests that they are biologically different from classically HER2/neu-amplified cases and which validates the 2018 ASCO/CAP guideline against automatically classifying such cases as HER2/neu amplified. •Breast cancers with HER2/CEP17 ratio of 2 or greater and HER2 copy number less than 4 account for 1.5% of breast cancers.•Sixty-one percent of breast cancers with HER2/CEP17 ratio of 2 or greater and HER2 copy number less than 4 are HER2 negative by IHC.•None of the breast cancers with HER2/CEP17 ratio of 2 or greater and HER2 copy number less than 4 were HER2 positive by IHC.•The findings are supportive of the 2018 ASCO/CAP guideline classifying these cases as HER2 negative.